JuxtaPosition : Skulptur. (Kobenhavn : Udstillingsbygningen ved Charlottenborg, 1993)
Andersen, Henrik B. ; Breivik, Bard ; Cavén, Kari ; Davey, Grenville ; Förg, Günther ; Genzken, Isa ; Gislason, Olafur ; Gudmundsson, Kristján ; Iglesias, Cristina ; Jensen, Soren ; Juvonen, Jari ; Löfdahl, Eva ; Melin, Truls ; Muñoz, Juan ; Nygard, Oivind ; Opie, Julian ; Ortwed, Kirsten ; Spalletti, Ettore ; Straede, Morten ; Toubro, Elisabeth ; Vercruysse, Jan
JuxtaPosition : Skulptur / Sculpture, Udstillingsbygningen ved Charlottenborg, Kobenhavn, 29. april - 6. Juni 1993
boek